Population and environment in Indonesia - Ida Bagoes Mantra (Indonesian Journal of Geography, 1991)
The present environmental situation is not compatible with our expectations. Pollution, erosion, floods and droughts have hit many parts of the world, and these disasters give us reflections on how serious are the environmental problems that befalls this planet of ours. In meeting its needs, mankind has exploited the environment to the utmost without caring about environmental conservation. Moreover, with the population explosion after the 1950s and the dependency of life upon the natural processes, the cultivated land to be inherited by future generations has gradually become increasingly barren and fertile.Efforts are absolutely necessary to check increasing population growth rates, to raise the standard of living for all people and to arouse and awareness of sustainable development policies so that a compability between development activities and environment can be achieved.